Analisis kesiapan profesi akuntan dalam era adaptasi kebiasaan baru - Inna Zahara; David Ulistiyantoro; Gerlan Haha Nusa (LPMP Imperium, 2022)
This research aims to determine the standard of skills needed to be involved in the accounting profession in the era of new habits (new normal) adaptation. The standard is in line with data on job market demand for beginners in the accounting profession disclosed on the job market job sitedepnaker. The population and sample of the study were ten job openings, including the categories